Implantation of a MitraClip between two previously implanted MitraClips to treat recurrent severe mitral regurgitation. Issue 2 (February 2017) - Lesevic, Hasema; Sonne, Carolin; Kasel, Albert Markus; Breuer, Dietmar; Kastrati, Adnan; Schunkert, Heribert; Ott, Ilka
Abstract: We first describe the implantation of a MitraClip (Abbott Vascular, Abbott Park, IL, USA) between 2 previously implanted MitraClips to treat recurrent mitral regurgitation (MR). An 82-year-old male patient presented with dyspnea New York Heart Association NYHA class III due to recurrent severe MR 18 months after primarily successful implantation of 2 MitraClips. The initial procedure was performed to treat severe MR due to prolapse and flail of the anterior leaflet and resulted in mild MR after implantation of 2 MitraClips. Concomitant diseases were persistent atrial fibrillation, moderate tricuspid valve regurgitation, and chronic kidney disease stage 3. Thus, the patient was not considered a suitable candidate for surgical treatment. Using fluoroscopic guidance, 2D- and 3D-transesophageal echocardiographies, we succeeded in placing a third clip between the previously implanted clips and reduced the severe MR to mild MR without increase in the mean gradient. No periprocedural complications were observed. Six months after the procedure the patient presented with mild MR and NYHA class I. <Learning objective: Implantation of MitraClips offers the possibility of percutaneous mitral valve repair. It is feasible, safe, and effective to implant a 3rd MitraClip between 2 previously implanted MitraClips to treat recurrent mitral regurgitation between the clips.>